جريمة الغش الضريبي وآليات مكافحتها في التشريع الجزائري - قريشة، محمد; قديري، إلهام; عبد الستار ،آمنة (جامعة الوادي University of El Oued, 2024)
الملخص: يعتبر الغش الضريبي من أخطر الجرائم وأكثرها إضرارا بأموال الدولة وسياستها الاقتصادية و ذلك في الوقت الذي لاقت فيه الجرائم الضريبية إحجاما من طرف الفقه عن إعطاء دراسات مستفيضة عنها بالإضافة إلى ندرة الممارسة القضائية والمتابعات عن هذا النوع من الجرائم على المستوى المحلي، الأمر الذي يدعو إلى وجوب توجيه الإهتمام نحو هذا النوع من الجرائم وإعطائها نصيبا من الدراسة و هو الهدف المنشود من خلال هذا العمل. لقد حاولنا معالجة الموضوع بالتعرض إلى ماهية الغش الضريبي بما أنه يشكل محل الجريمة وتكييفه القانوني والتعرف كذلك على أبرز الأسباب التي أدت إليه ومختلف الأساليب المستعملة من أجل التخلص من أداء الضربية والآثار المنجرة عنه هذا من جهة. ومن جهة أخرى تناولنا آليات مكافحة التهرب الضريبي من خلال معالجة أسبابه عن طريق وسائل وقائية ورقابية. كما تطرقنا إلى الوسائل القمعية بالرجوع إلى السياسة العقابية التي اتبعها المشرع الجزائري في كل من المواد الجزائية والجبائية من أجل إخضاع المكلفين بالضريبة لتطبيق وتنفيذ الالتزامات الجبائية واحترامها. بعدما قمنا بإعداد موضوعنا الذي يندرج ضمن الغش الضريبي وأليات مكافحته في التشريع الجزائري بحيث تعرفنا على ماهية الغش وما الأسباب التي تؤدي إليه والآثار التي تخلفها جريمة الغش الجبائي بحيث قامت الإدارة الضريبية بمكافحتها عن طريق وسائل وسياسة تمكن اعوانها من الحد من هاته الجريمة التي قد تؤثر على إقتصاد الدولة ومن المعلوم أن الضرائب تشكل الممول الأساسي للخزينة العمومية، ولكن من جهة أخرى نجد المكلفين بها يسعون دائما إلى تفاديها بشتى الطرق وهذا ما يعرف بالغش الضريبي والجزائر كغيرها من دول المغرب العربي وحتى باقي بلدان العالم تعاني من هذه الظاهرة، وقد حاولنا من خلال هذه المذكرة أن نجري عرض الغش الضريبي واليات مكافحته في التشريع الجزائري بخصوص سياسات مكافحة الغش الضريبي لمعرفة هاذا الأخير ومدى نجاعتة طرق المكافحة ، والتأكد من وجود تعاون بين المكلف بالضريبة والإدارة في هذا الإطار، بالإضافة لإحتياج الدولة لهذا المصدر . Tax fraud is considered one of the most dangerous crimes and the most harmful to the state’s funds and economic policy. At a time when tax crimes have met with reluctance on the part of jurisprudence to provide extensive studies on them, in addition to the scarcity of judicial practice and follow-up on this type of crime at the local level, which calls for the necessity of... Directing attention towards this type of crime and giving it a share of study, which is the goal sought through this work. We have tried to address the issue by examining the nature of tax fraud, since it constitutes the subject of the crime and its legal context, and also identifying the most prominent reasons that led to it and the various methods used in order to get rid of the tax payment and the effects resulting from it, on the one hand. On the other hand, we discussed mechanisms for combating tax evasion by addressing its causes through preventive and supervisory means. As we touched on repressive means by referring to the punitive policy followed by the Algerian legislator in both penal and criminal matters. Taxation in order to subject taxpayers to the application, implementation and respect of tax obligations. After we prepared our topic, which falls within tax fraud and the mechanisms for combating it in Algerian legislation, so that we learned what fraud is, the reasons that lead to it, and the effects left by the crime of tax fraud, so that the tax administration combated it through means and policies that enable its agents to reduce this crime that may affect the economy. the country and It is known that taxes constitute the primary fund for the public treasury, but on the other hand, we find those charged with them always seeking to avoid them in various ways, and this is what is known as tax fraud. Algeria, like other countries of the Maghreb and even the rest of the world, suffers from this phenomenon, and we have tried through this memorandum to We are presenting tax fraud and the mechanisms for combating it in Algerian legislation regarding policies for combating tax fraud in order to know the latter and the effectiveness of the methods of combating, and to ensure that there is cooperation between the taxpayer and the administration in this context, in addition to the state’s need for this source.
ماستر اعمال